Efficacy and safety in 1% clotrimazole powder, adjuvant therapy in patients with superficial fungal cutaneous infection in intertriginous areas - Rasthawathana Desomchoke (2018)
© 2016, Medical Association of Thailand. All rights reserved. Background: Superficial fungal cutaneous infection is commonly found in intertriginous area. Objective: To assess 1% clotrimazole powder (1% CP) efficacy for adjuvant treatment of superficial fungal cutaneous infection in intertriginous areas. Material and Method: The study performed as an open-label, randomized, comparative study for evaluating the effects of 1% clotrimazole cream (1% CC) with 1% CP in patients infected with dermatophytes (DMPs) or Candida spp. in intertriginous area, comparing to patients treated with 1% CC as control by demonstrating complete cure rate at 4, 8, and 12 weeks as well as relapse rates during a 24-week period including patient satisfaction. Results: Sixty-seven patients with mean age of 54.6 years were included in this study. Of those, 61.2% were males. Thirty-five patients were infected with DMPs and 32 with Candida spp. The complete cure rates of experimental group were significantly higher than the control group, as observed within four weeks (p = 0.01), especially for dermatophyte infection (p = 0.039). Two cases had recurrent candidiasis in the control group. In both groups, relapse up to 24 weeks were not statistically different. Additionally, there was no difference in patients’ satisfaction towards convenience of drug application. Conclusion: Using of the 1% CP could be suggested as an adjuvant therapy and possibly preventive agent for superficial fungal cutaneous infection in intertriginous areas.